The dynamics of Indonesian migrant worker placement in 2024: challenges and competence enhancement strategies in the global labour market - Afriansyah Noor; Alfitri; Kiagus Muhammad Sobri; Abdullah Qiqi Asmara; Muhammad Izzudin (Penerbit Universiti Kebangsaan Malaysia, 2025)
This article explores the current conditions and strategic challenges faced by Indonesian Migrant Workers (PMI) in 2024, with a particular emphasis on placement trends, labor market dynamics, and the implications for national policy. Drawing on recent statistical data and reports from credible institutions, the study reveals a significant decline in PMI placements as of July 2024 compared to the same period in the previous year. Notably, the migration flow continues to be gendered, with female workers representing the majority of placements. These workers are primarily employed in Asian countries, including Hong Kong, Taiwan, Malaysia, Japan, and Singapore, which remain the dominant destination markets for Indonesian labor export. The analysis further indicates that domestic sectors especially roles such as housemaids and caregivers still constitute the largest proportion of job placements. This sectoral concentration raises concerns about job vulnerability, limited upward mobility, and the potential for exploitation, particularly among low-skilled workers. The findings point to an urgent need for the Indonesian government to implement more comprehensive and forward-looking policies that enhance the education, vocational training, and digital literacy of PMI. By improving the skill base and resilience of migrant workers, Indonesia can better position its labor force in the increasingly competitive and regulated global labor market. The study concludes by offering recommendations for policy development aimed at ensuring the long-term protection, empowerment, and global competitiveness of PMI.